IMPLEMENTASI PERATURAN DAERAH KABUPATEN PATI NOMOR 9 TAHUN 2008 TENTANG GARAM KONSUMSI BERYODIUM - Destiara Prahastiwi; Achmad Taufiq; Rina Martini (Journal of Politic and Government Studies, 2015)
Pati Regency is number one salt supplier in Central Java but it doesn’t guarantee the quality. Iodine Deficiency Disorders (GAKY) in Central Java is suspected because the salt produced in Pati Regency does not meet the quality standards of iodized salt. GAKY problems is a serious issue considering the danger affect life sustainability and human resource quality. The problem with under standard quality of iodized salt has urged the Regency’s government to issue Local Regulation no. 9 in 2008 about Iodized Consumption Salt. The issue means one step forward to regulate the existence of salt industry and customer protection. The regulation has also placed a legal stepping stone against the violations of existing regulations.Method of the research is qualitative. In this research, author conducted descriptive-analytic research which aims to reflect, describe or picture systematically, factually and accurately over facts, characteristics as well as associations of the phenomenon studied. To collect data, author use purpose sampling method and conducted interviews with the Development Planning Agency at Sub-National Level (Bappeda) of Pati Regency, Health Department of Pati Regency, Industry and Commerce Department of Pati Regency, salt manufacturers in Pati Regency and the Head of APROGAKOB of Pati Regency.Local Regulation no. 9 year 2008 about Iodized Consumption Salt came into effect 6 (six) months after being established in December 17, 2008. The six-month deadline given by the government is used to socialize the regulation to the entire salt manufacturers in Pati Regency as the regulation target. They are directed to obey the regulation not only to produce iodizedsalt of 30 ppm – 80ppm but also starting from the washing of the materials, drying, iodine mixing, oven process and packing. However, the main problem faced by the manufacturers is the iodine content. The implementation of the Local Regulation is to emphasize the quality of iodized salt according to the standart. Given the fact over the years since the regulation has come into effect, the level of manufacturers’ compliance has increased significantly. In 2011 – 2012, only 28,5% of manufacturers have met ppm standard. In 2013, it drastically increased to level 64,89% of manufacturers who have met the ppm standard. In 2014, the number ixmproved to 69,48%.Author recommends the salt manufactures should increase the quality. Firmness in the enforcement of the regulation to provide a deterrent effect on manufacturers who do not comply and underestimate the government. Coaching, supervision, quality control management, socialization and unannounced visits should be enhanced to remind the salt manufacturers to produce good quality of iodized salt according to standard.Key words: Policy Implementation, Local Regulation no. 9 year 2008 about Iodized Consumption Salt